Synthesis and Characterization of Magnetic Chitosan-L-Dopa Nanocomposite - Suzariana Samuri, Nor; Hasan Hussein-Al-Ali, Samer; Kura, Aminu; Zobir Hussein, Mohd; Fakurazi, Sharida; Halim Shaari, Abdul (Current Nanoscience, 2016)
Background: The aim of this study is to design a new levodopa nanocomposite. A levodopa (dopa)- iron oxide nanoparticles (MNPs) nanocomposite was synthesized under an high basic environment using dopa, FeCl3 and FeCl2 as the precursors. Methods: iron oxide nanoparticles (MNPs) were prepared using an iron salt coprecipitation method in a sodium hydroxide medium and subsequently coated with the bioavailability polymer chitosan (CS) to form CS-MNP nanoparticles. CS-MNP was loaded with levodopa to form a dopa-CS-MNP nanocomposite. Results: A magnetization study shows that both MNPs and the dopa-CS-MNP nanocomposite were superparamagnetic with saturation magnetizations at 25 and 30 emu/g, respectively. The levodopa release was also studied at 25 and 37 °C with carbonic anion and showed 90 % release over 1000 minutes. The mean diameters of MNPs and dopa-CS-MNP are 57 nm and 43 nm, respectively. The cytotoxicity effects in normal cells (3T3) were investigated using an MTT assay for up to 72 hours. The IC50 values of dopa-CS-MNP and free dopa are 199 ±2 μg/ml and 40 ±2 μg/ml, respectively. Conclusion: The resulting dopa-CS-MNP nanocomposite can be used in a wide range of applications, such as biotechnology, MRI and drug delivery.
Keywords: 3T3 cells